1999
DOI: 10.1016/s0022-5347(05)69001-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Responses Evoked by Lower Urinary Tract Stimulation in Superior Cervical Ganglion Cells in the Rat

Abstract: Reflexes from the lower urinary tract clearly reached sympathetic neurons located in remote segments. The response incidence in the population studied suggests that most sympathetic neurons involved in cardiovascular regulation participate in these reflexes. The different reflex patterns probably occur in neurons with different functional targets in the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Controversial results were reported concerning the activity of afferent neurons in the urinary tract evoked by bladder distension, which could trigger both excitatory and inhibitory reflexes (Habler et al 1999). Different bladder afferent activity was shown by the cuff electrode recordings from pelvic nerve during the changes in bladder pressure (Rocha et al 2001, Jezernik et al 2000.…”
Section: Urinary Bladder Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial results were reported concerning the activity of afferent neurons in the urinary tract evoked by bladder distension, which could trigger both excitatory and inhibitory reflexes (Habler et al 1999). Different bladder afferent activity was shown by the cuff electrode recordings from pelvic nerve during the changes in bladder pressure (Rocha et al 2001, Jezernik et al 2000.…”
Section: Urinary Bladder Experimentsmentioning
confidence: 99%
“…Vascular disorders were studied by morphometry and immunohistochemistry (Matsumoto et al 2003). Activation of the afferent signals from the urinary bladder were examined with different methods, including systemic blood pressure and heart rate measurements, neurological study of reflexes, and direct recordings of neural activity (Mehnert et al 2009, Weaver 1985, Rocha et al 2001, Habler et al 1999, Jezernik et al 2000, Hubeaux et al 2007, Carly et al 2009. Thus, a lot of methods are known to individually study vesical neural activity and circulation in situ and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo intracellular recording from the rabbit SCG (Skok and Ivanov, 1983) and rat SCG (McLachlan et al, 1997, 1998; Habler et al, 1999) has shown that naturally occurring subthreshold nicotinic EPSPs may contribute to postganglionic firing. Although consistent with the gain hypothesis, an alternative interpretation has been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in synaptic activity in various neurones of rat SCG occurred in response to cutaneous nociceptor stimulation (brief pinches, McLachlan et al 1997) and bladder distension (Häbler et al 1999), and were linked to respiration (McLachlan et al 1998) and/or changes in arterial blood pressure (Fig. 3).…”
Section: Intracellular Recording In Vivomentioning
confidence: 99%